Sensitivity of sheltered mudflats to wind events - Zhu, Qin; Nie, Wei; Zhu, Zhenchang; Cai, Yanpeng; Yang, Zhifeng (Frontiers in Earth Science, 2022)
The impact of waves on the morphological changes of sheltered mudflats is less well studied compared to that on open flats. To investigate the sensitivity of low-energy sheltered mudflats to hydrodynamics such as waves, we carried out in situ measurements of bed level, currents, and waves on the middle flat of a sheltered mudflat in a bay in southern China. Two one-month measurements, March 26 – April 26, 2021, and July 8 – August 8, 2021, were performed for repetition. We found that the sheltered system was not as stable as it appeared. The maximum intratidal bed-level variation, ΔZ, was <5 mm in calm conditions. However, wind speeds slightly highly than 3.0 m/s, under which significant wave height was approximately 0.1 m, triggered significant bed-level variation patterns, with ΔZ reaching up to 2 cm. Intratidal bed-level change patterns depend on the relative dominance of waves and currents: low τc (current-induced bed shear stress) and high τw (wave-induced bed shear stress) promote the generation and migration of bed ripples; comparable τc and τw, with medium-to-high values, lead to non-cyclic bed-level change patterns; high τc and high τw result in bed accumulation/degradation superimposed by bed ripple migration. From a long-term perspective, i.e. in the time scale of month to year, sheltered mudflats are stable systems, and their high sensitivity causes short-term significant bed-level variation. The sensitivity and stability of sheltered mudflats must be further investigated to explore the effects of human intervention and global climate change.